A tale of four prostates. Issue 2 (21st March 2013) - Kirby, Roger; Hanbury, Damian; Anderson, John; Vesey, Sean G.
Abstract Four urologists relate their personal experiences of prostate cancer and highlight some important learning points. Copyright © 2013 John Wiley & Sons